Adaptive Global WASF-GA to Handle Many-objective Optimization Problems - González-Gallardo, Sandra; Luque-Gallego, Mariano; Saborido Infantes, Rubén; Ruiz-Mora, Ana Belén (Elsevier, 2020)
In this paper, a new version of the aggregation-based evolutionary algorithm Global WASF-GA (GWASF-GA) for many-objective optimization is proposed, called Adaptive Global WASF-GA (A-GWASF-GA). The fitness function of GWASF-GA is defined by an achievement scalarizing function (ASF) based on the Tchebychev distance, which considers two reference points (the nadir and utopian points) and a set of weight vectors. Despite of the benefits of using these two reference points simultaneously and a well- distributed set of weight vectors, it is necessary to go a step further to get better approximations in problems with complicated Pareto optimal fronts. For this, in A-GWASF-GA, some of the weight vectors are re-calculated during the optimization process based on the sparsity of the solutions found so far, and taking into account some theoretical results demonstrated in this paper regarding the ASF considered. Different strategies are carried out to accelerate the convergence and to maintain the diversity. The computational results, carried out in comparison with NSGA-III and different versions of MOEA/D, show the good performance of A-GWASF-GA in well-known but also in novel many-objective optimization benchmark problems.
Keywords: Optimización; Many-objective optimization; Pareto optimal solutions; Achievement scalarizing function; Evolutionary algorithm; Weight vectors